Microbial precipitation of Pb(II) with wild strains of Klebsiella Pneumoniae and Paraclostridium Bifermentans isolated from an industrially obtained microbial consortium - Brink, Hendrik Gideon (University of Pretoria, 2023)
Dissertation (MEng (Chemical Engineering))--University of Pretoria, 2022.